Processing and Storage Impact on Carotenoid Contents and Functional Properties of Yellow Cassava Traditional Food Products - Mopelola, Lawal, Oluranti; Adebanjo A, Badejo; Nathaniel, Fagbemi Tayo (Journal of Food Technology Research, 2020)
This study determined the carotenoid content, functional properties and sensory qualities of seven cassava products (Dried chips, Attieke, Chickwangue, Fufu, Gari, Lafun and Pupuru) obtained from yellow fleshed biofortified cassava varieties (TMS 01/1371, TMS 01/1412 and TMS 01/1368) before and after processing over a 3months period of storage. Cassava products obtained from the three varieties were analysed and compared with non biofortified products. Bulk density was highest at 0.92 g-1ml in variety TMS01/1412 and lowest at 0.57 g-1ml in TMS 01/1371. Swelling capacity ranged from 25.67-51.33% while Water absorption capacity ranged from 19.33-75.33% across all the biofortified products. Carotenoid content decreased after processing and even much more after storage but modest retention recorded in variety TMS 1368. Retention of total carotenoid after the storage period was highest in Chickwangue (95%) and Fufu (92%) for variety TMS01/1368 and lowest in lafun from TMS 01/1371(25%). Overall acceptance of food products from variety 01/1368 was significantly higher among the samples hence, have potential to be the choice of biofortified cassava variety for production of cassava based food products with high retention of total carotenoid content.